Understanding the "blue spot": Sodium chloride hot salt stress-corrosion cracking in titanium-6246 during fatigue testing at low pressure. (March 2016) - Saunders, E.A.; Chapman, T.P.; Walker, A.R.M.; Lindley, T.C.; Chater, R.J.; Vorontsov, V.A.; Rugg, D.; Dye, D.
Abstract: During hot component fatigue tests there have been two cases of low life crack initiation of gas turbine rotating parts manufactured from the Titanium alloy Ti-6246. Both exhibited a small (~ 0.1 mm) elliptical 'blue spot' at the origin. Through validated striation count work and fracture mechanics it was established that fatigue had propagated with a near-nil initiation life. Early investigation suggested that the 'blue spot' was possibly a region of stage 1 fatigue growth, and was therefore a material behaviour concern with potential implications for service. During an investigation of a later cracking incident in this alloy, subsequently shown to have resulted from stress-corrosion cracking (SCC), near-identical fractographic characteristics to that seen in the "blue spot" were found that subtly differentiated it from stage 1 fatigue. Also, similar 'blue spots' have since been identified on Ti6246 Laboratory hot LCF test specimens and found to have been due to contamination by NaCl, through the application of focussed long-term EDX examination and other novel chemical analyses techniques. By the application of those techniques, fractography, and comparison against these specimens, Rolls-Royce and Imperial College London have collaborated to show that the original two component 'blue spots' were subtle examples of NaCl-related Hot Salt Stress-Corrosion Cracking (HSSCC). Such cracking has not been found to occur in service components, due to air pressure within the engine, and the effect is therefore confined to Laboratory and component tests at near-atmospheric pressure or below. Highlights: Low life crack initiation from small optically blue spots at fatigue origins, Ti-6246 Near-nil initiation life from validated striation counting and fracture mechanics Blue spots established as subtle examples of NaCl hot salt stress-corrosion cracking. Advocated by focussed EDX, FIB-SIMS and STEM-EDX on fracture surface FIB lifted foils. Lack of in-service implication under the high pressures of gas turbine environments